A 3D map of the Milky Way's disk as traced by classical Cepheids. Issue Volume 14:Issue S353(2019) (June 2019) - Chen, Xiaodian; Wang, Shu; Deng, Licai; de Grijs, Richard; Liu, Chao; Tian, Hao
Abstract: We have collected 2330 Cepheids to establish an intuitive 3D map of the Milky Way's disk. As regards the warp amplitude, the Cepheid disk agrees well with the gas disk for radii up to 15 kpc. However, the mean line of nodes (LON) of the Cepheid disk deviates from the Galactic Center–Sun direction by 17.5±1.0°. This is a new and different result compared with previous results. The LON is not stable at any given radius, but it twists. The twisted pattern suggests that the formation of the Milky Way's warp is dominated by the massive inner disk. The kinematic warp defined by the Cepheids is also in concordance with the spatial warp. In the 2020 era, the anticipated increasing number of new Cepheids will provide a key opportunity to view our Milky Way's disk as a whole, and we expect that our knowledge of the disk's main structural features will be much improved.